1997
DOI: 10.3109/02841869709100738
|View full text |Cite
|
Sign up to set email alerts
|

Extrapulmonary Small Cell Gastric Carcinoma:A Case Report and Review of the Literature

Abstract: Extrapulmonary anaplastic small cell tumours (EPSCC) of the gastrointestinal tract are generally aggressive neoplasms with a poor prognosis. Recent work has demonstrated that EPSCC may be sensitive to the chemotherapeutic regimens employed to treat small cell lung cancer.In this report we present the case of a patient with a primary anaplastic small cell gastric carcinoma treated with combination chemotherapy. Plasma calcitonin, somatostatin, gastrin releasing peptide, total enolase and non-muscle creatine kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 18 publications
1
17
0
1
Order By: Relevance
“…The median survival was described in the range of 6 -12 months or of several weeks, for treated or untreated patients, respectively (Redman and Pazdur, 1987;Wick et al, 1987;O'Byrne et al, 1997). In our study, all but two patients were treated; the median survival was 11 months and 2-year survival was 23%.…”
Section: Discussionsupporting
confidence: 44%
“…The median survival was described in the range of 6 -12 months or of several weeks, for treated or untreated patients, respectively (Redman and Pazdur, 1987;Wick et al, 1987;O'Byrne et al, 1997). In our study, all but two patients were treated; the median survival was 11 months and 2-year survival was 23%.…”
Section: Discussionsupporting
confidence: 44%
“…Concerning treatment, because of the tumor's aggressive biological characteristics, intensive chemotherapy, with or without operation, is recommended for gastric ECC at any stage [44]. Previously, several chemotherapeutic menus have been employed for gastric ECCs, but their effectiveness has been shown in only a few patients [32,46,55]. Sakai et al [32] showed complete remission in a 31-year-old man with gastric ECC with multiple bone metastasis (case 29 in Table 1), with seven cycles of chemotherapy consisting of cisplatin (CDDP), etoposide, cyclophosphamide, epirubicin, and vincristine, followed by high-dose chemotherapy and peripheral blood cell transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Role of surgical resection in SCLC is limited with treatment being primarily combined chemoradiation [54] . However, SCC has also been described in various other parts of the body including the gastro-intestinal tract, male and female genital tract, musculoskeletal system and others [5,15,[55][56][57] . Extrapulmonary SCLC, especially in the lymph nodes, is an extremely rare entity.…”
Section: Discussionmentioning
confidence: 99%